Rattus fuscipes Waterhouse 1839 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Rattus fuscipes Waterhouse 1839 Rattus fuscipes Waterhouse 1839, Zool. Voy. H. M. S. "Beagle", Mammalia: 66. Type Locality: Australia, Western Australia, Albany, "Little Grove" on Princess Royal Harbor, 4 mi (6 km) S Mt Melville (as restricted by neotype designation by Taylor and Horner, 1973; also see Mahoney and Richardson, 1988). Vernacular Names: Australian Bush Rat. Synonyms: Rattus assimilis (Gould 1858); Rattus brazenori Tate 1940; Rattus coracius Thomas 1923; Rattus glauerti Thomas 1926; Rattus greyii (Gray 1841); Rattus manicatus (Gould 1858); Rattus mondraineus Thomas 1921; Rattus murrayi Thomas 1923; Rattus peccatus Troughton 1937; Rattus pelori Finlayson 1960; Rattus ravus Brazenor 1936. Distribution: Coastal, subcoastal, and offshore islands of SW Western Australia; S coast from Eyre Peninsula in South Australia (Robinson et al., 2000) to W Victoria; coastal and subcoastal Victoria from Otway Peninsula north to near Rockhampton in Queensland; coastal Queensland from Townsville to Cooktown (Lunney, 1995 a :652; Seebeck, 1995 c :225; Taylor and Horner, 1973:15). Conservation: IUCN – Lower Risk (lc). Discussion: Rattus fuscipes species group. Taylor and Horner (1973) suggested, on morphological grounds, that the Queensland population of R. fuscipes ( coracius ) has a common ancestry with Queensland R. leucopus , a hypothesis reasserted by Taylor et al. (1982, 1983). This relationship, however, is unsupported by either chromosomal (Dennis and Menzies, 1978) or allozymic data (Baverstock et al., 1983 a , 1986). Reviewed by Taylor and Horner (1973), Watts and Aslin (1981), Mahoney and Richardson (1988), and Lunney (1995 a ). See Taylor and Calaby (1988 a , Mammalian Species, 298). The name manicatus was included in the synonymy of Rattus fuscipes by Taylor and Horner (1973), but listed as incertae sedis by Mahoney and Richardson (1988:192). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Rodentia - Family Muridae, pp. 1189-1531 in Mammal Species of the World: a Taxonomic and ...